Peran Proses Pengadaan dan Kontrak dalam Rancang Bangun Operasional Teknologi Informasi Bank Sentral Melalui Sistem Outsourcing SDM - Tjiptogoro Dinarjo (Institut Ilmu Sosial dan Manajemen STIAMI, 2014)
The role of outsourcing is very strategic, therefore we needs to have an outsourcing system to optimally support the Information Technology (IT) services that are drived from and integrated with information system and business strategy. The objective of this research is to formulate a model of development of IT services through outsourcing system. This model expected to assist the management in making strategic Human Resources (HR) Policies in line with the institutional strategy and business. The specific objectives of research: analyzing the dominant factors affecting the development of IT services through outsourcing system; analyzing the relations between such factors with the outsourcing success to achieve prime services; analyzing the model forms of development; and producing the model of development. This Case study was conducted in BI, by applying the approach of integrated explorative, descriptive and explanatory researches, analysis for endogen and exogen variables by applying Structural Equation Modeling (SEM). Policy model was formulated based upon the SEM analysis’s result, then some verification and validation were done through Individual Depth Interview (IDI) and Focus Group Discussion (FGD). This study indicated that the key success factors of outsourcing system in supporting IT services are: (1). capability with indicators quality technical personnel, product efficiency, technical process, process management, quality control, service quality and project management; (2). procurement process with indicators: service quality, competition, cost, cooperation, and froud act; (3). contract with indicators: incentive, penalty, trust, preventing froud act, and cooperation; (4). outsourcing implementation with indicators: cooperation, sustainable expectation, partnership, investment intention, commitment and power client. But In this case, how ever focus analysis on: (1). procurement process with indicators: service quality, competition, cost, cooperation, and froud act; (2). contract with indicators: incentive, penalty, trust, preventing froud act, and cooperation: